Gestión financiera de cobranzas del gobierno autónomo descentralizado del cantón Riobamba, y la recuperación de cartera vencida del período 2017 - Tonny Ricardo, Rosero Guadalupe (2019)
Nowadays it is very important to have an adequate administration of economic resources within an organization, and this will depend a lot on decisions that are taken which could affect or benefit the same, allowing in this way to have a better control and at the same time to be able to evaluate the performance of the organization, allowing it to face the economic and financial changes that present themselves today. It is consequently that the present work called "Financial Management of Collections of the Autonomous Decentralized Government of Riobamba Canton, and the Recovery of Expired Portfolio of the Period 2017", is oriented as a dynamic instrument to detect the corrective actions for the processes of continuous improvement of the GADM Riobamba. To this end, the research background and a state of the art have been developed to support theories on which the research work is based. In the present research work, a horizontal analysis, application of indicators and flow of processes related to the problem, obtaining results based on the objectives set, the methods and techniques predicted for the development of the work. And it should be noted that the establishment of credit policies and rigid collections to reduce the rate of delinquency, perform at least one financial analysis per period in order to improve and evaluate the management and performance of GADM Riobamba within the economic sphere.